Association of Low-Density Lipoprotein Receptor-Related Protein 1 and Its rs1799986 Polymorphism With Mild Cognitive Impairment in Chinese Patients With Type 2 Diabetes - Cao, Wuyou; Tian, Sai; Zhang, Haoqiang; Zhu, Wenwen; An, Ke; Shi, Jijing; Yuan, Yang; Wang, Shaohua (Frontiers in Neuroscience, 2020)
Background: Low-density lipoprotein receptor associated protein 1 (LRP1) plays roles in cerebral glucose metabolism and clearance of amyloid-β. This study aims to investigate the pathogenetic roles of LRP1 and its rs1799986 polymorphism in mild cognitive impairment (MCI) among type 2 diabetes (T2DM) patients. Methods: 166 Chinese T2DM patients were enrolled and divided into two groups according to Montreal Cognitive Assessment score. Neuropsychological tests were performed, the soluble LRP1 (sLRP1) concentration was assessed using ELISA, genotype of LRP1 rs1799986 was detected using sequenom method. Results: 60 diabetic-MCI patients displayed significantly lower plasma sLRP1 levels (p=0.033) and poor glucose control (p=0.009) than their healthy-cognition controls (n=106), and plasma sLRP1 levels (OR=0.971, p=0.005) and HbA1c (OR=1.298, p=0.003) are both risk factors for diabetic-MCI patients in addition to use of insulin and hypertension, but association of plasma sLRP1 levels and HbA1c was not found. Their plasma sLRP1 concentrations negatively correlated with Stroop Color Word Test B Number (r=-0.335, p=0.011), which represents measure selective attention, cognitive flexibility and processing speed. Additionally, T allele carriers of LRP1 rs1799986 showed higher MMSE scores and AVLT delayed recall scores (p=0.025; p=0.025 respectively) in T2DM patients. Conclusion: In T2DM patients, lower plasma levels of sLRP1 portend the early cognitive deficits, especially attention dysfunction. Further study is needed to elucidated the roles of LRP1 in hyperglycemia induced cognitive declines. T allele of LRP1 rs1799986 probably decreases the MCI susceptibility.